The dragon and the boar ebook - Sharp, Liam (Starhenge,, 2023)
Revered creator LIAM SHARP cuts loose in his visually stunning masterpiece, STARHENGE, BOOK ONE: THE DRAGON & THE BOAR! A future MERLIN travels to 5th-century Britain to prevent monstrous time-traveling killer robots from robbing the universe of magic! Meanwhile, Amber Weaver’s lively present-day narrative reveals how she becomes drawn into a war across time. The Terminator meets The Green Knight in this enthralling epic inspired by the Arthurian sagas!